Community Training in the Utilization of Alfukat Plants with a Grafting System in Bangko Hamlet - Syafi, Sartika; Abdullah, Hayun; Samad, Sofyan; Soenarsih, Sri (Agrikan Jurnal Agribisnis Perikanan, 2023)
Greening the yard is one of the actions that can tolerate the greenhouse effect and global warming, the utilization of yard land can increase fresh air, support the household economy and reduce pollution. Planting fruit trees is one of the solutions to reduce global warming. Fruit plants can be propagated vegetatively using a grafting system to shorten the reproductive period. The objectives of this research are to: 1) To increase public interest in fruit plants with grafting systems, and 2) to provide information about fruit plants with grafting systems. The research was conducted in bangko hamlet, Bobane Igo Village, West Halmahera Regency. The types of data collected in this research are primary and secondary data. The results showed that the public interest is very large to know about the grafting system on fruit plants. The failure of grafting of fruit plants can be caused by one of them is dependent on temperature and climate, how to take sample time, and the age of the saplings.